Impact of continuing anti-platelet drugs during manual small incision cataract surgery under subtenon’s anesthesia in tertiary care in South India - Divya P; Ajay K; Shweta Sulabh; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2025)
Background: Antiplatelet drugs are routinely used in elderly patients with atherosclerotic diseases to prevent cardiovascular ischemic events such as acute coronary syndrome, myocardial infarction, or stroke. While various studies have established the safety of continuing anti-platelet drugs during phacoemulsification. Hence, the current study was undertaken. Aims and Objectives: To observe the impact of continuing anti-platelet drugs during manual small incision cataract surgery (MSICS) under subtenon’s anesthesia in tertiary care in South India. Materials and Methods: Patients undergoing small incision cataract surgery in a medical college in South India from August 2024 to December 2024 were part of the study after obtaining written informed consent. They were randomly assigned to two groups. Group1-patients taking antiplatelet drugs for a thromboembolic disorder and Group 2-patients not on antiplatelets drugs. MSICS was performed under subtenon’s anesthesia using a blunt cannula (no sharp needle prick). Patients were monitored intraoperatively, postoperatively on day 1, day 7, and 30 for any ocular hemorrhage and thromboembolic events. Results: Incidence of hemorrhagic complications was 46% in group 1 and 26% in the control group on the first post-operative day. The subconjunctival hemorrhages resolved spontaneously, and there was no difference between the two groups at the end of 1 month post-surgery. There was also no difference in the final best-corrected visual acuity between the two groups. The hemorrhages that occurred were self-limiting and visually insignificant. No patient had a retrobulbar, vitreous, choroidal hemorrhage, or a sight-threatening complication. No thromboembolic events were noted in the 1-month post-operative period. Conclusion: The present study results explain that it is safe to continue antiplatelets in MSICS performed under subtenon anesthesia by an experienced surgeon.